"A good socket fit can make you or break you": A multimethod study to explore the perceptions and experiences of socket fitting among people with lower-limb loss in Australia. - Armitage, Lucy; Kark, Lauren; McDonald, Kirsty A.; Sparke, Darrel; Ford, Belinda (Prosthetics & Orthotics International, 2025)
Background: Iterative design and modification are used to manufacture lower limb prosthetic sockets that meet users' needs while also fulfilling safety and mobility criteria. Greater understanding of the expectations of prosthesis users regarding prosthetic fit as well as their experiences at the time of socket fitting is needed. Objectives: Describe lower limb prosthesis user perceptions and experiences of socket comfort and discomfort during their last fitting and compare this to their expectations for a perfectly fitting socket and their satisfaction with the socket they had fitted. Study Design: Mixed methods (quantitative and qualitative). Methods: A questionnaire was designed and administered in consultation with Amputees NSW (an amputee advocacy group) and distributed through their membership database. Qualitative responses were analyzed to explore prosthesis user experiences of socket fitting, general wear, as well as socket comfort, discomfort, and satisfaction. Quantitative responses were analyzed using descriptive, nonparametric methods. Results: Thirty participants with a range of lived experiences completed the questionnaire. Reported comfort and discomfort varied across participants and indicated that expectations and experiences of fit varied and changed over time, with some participants anticipating adjustment over time would be necessary. Qualitative analysis found experiences of prosthesis socket comfort/discomfort on the day of fitting and general experiences of socket comfort related to 2 key factors—the prosthesis itself and the individual prosthesis user. Conclusions: Understanding the experiences and expectations of prosthesis users for comfort and intended activities is central to ensure success of the socket fitting approach. Investigation into fit changes over time could provide insights into follow-up requirements, user education, and funding mechanisms.